Avian SERPINB12 Expression in the Avian Oviduct Is Regulated by Estrogen and Up-Regulated in Epithelial Cell-Derived Ovarian Carcinomas of Laying Hens - Jo, Gahee (Public Library of Science, 2014)
Serine protease inhibitors (SERPINs) are involved in a variety of biological processes such as blood clotting, angiogenesis, immune system, and embryogenesis. Although, of these, SERPINB12 is identified as the latest member of clade B in humans, little is known of it in chickens. Thus, in this study, we investigated SERPINB12 expression profiles in various tissues of chickens and focused on effects of steroid hormone regulation of its expression. In the chicken oviduct, SERPINB12 mRNA and protein are abundant in the luminal (LE) and glandular (GE) epithelia of the magnum in response to endogenous or exogenous estrogen. Furthermore, SERPINB12 mRNA and protein increase significantly in GE of cancerous ovaries of laying hens with epithelia-derived ovarian cancer. Collectively, these results indicate that SERPINB12 is a novel estrogen-stimulated gene that is up-regulated by estrogen in epithelial cells of the chicken oviduct and that it is a potential biomarker for early detection of ovarian carcinomas in laying hens and women.